FACTORS INFLUENCING GEN Z’S E-LOYALTY IN SHOPPING ON E-COMMERCE - Haryaji Catur Putera Hasman; Wan Rizca Amelia; Alfifto; Siti Alhamra Salqaura (CV. Radja Publika, 2023)
This study aims to analyze the factors that influencing Gen Z’s e-loyalty in shopping on e-commerce. The population in this study are residents of Medan city who belong to Gen Z who have shopped at least twice on the e-commerce platform. The sample in this study were 96 respondents, and used incidental sampling techniques. The data was analyzed using multiple linear regression with hypothesis proving through t-test and F-test. The results show that e-WOM has a positive and significant influence on e-loyalty, e-servqual has a positive and significant influence on e-loyalty, and e-satisfaction has a positive and significant influence on e-loyalty. And simultaneously e-WOM, e-servqual, and e-satisfaction have a positive and significant influence on e-loyalty.